Motivational profiles related to the academic satisfaction of university students - Vergara-Morales, Jorge; Del Valle, Milenko; Díaz, Alejandro; Matos, Lennia; Pérez, María-Victoria (Anales de Psicología / Annals of Psychology, 2019)
The aims of the study were to identify the motivational profiles of university students and to assess their differences according the academic satisfaction. The participants were 882 students aged 17 to 50, from nine Chilean universities. Motivational profiles were identified by cluster analysis, following the combination of hierarchical and non-hierarchical methods. The cluster analysis was perform including the following motivational variables: (1) autonomous motivation, (2) controlled motivation, (3) perception of autonomy support, and (4) perception of autonomy control. The differences among the profiles were assessed through the one way Anova test, considering the effect size calculation, and the Games-Howell post-hoc analysis. The cluster analysis results supported a four motivational profiles solution: poor quality (n = 167), low quantity (n = 144), good quality (n = 333), and high quantity (n = 238). Moreover, students grouped into profiles with higher levels of autonomy for learning, presented the highest levels of academic satisfaction. In conclusion, the importance of motivational factors to facilitate the development of university students’ well-being is highlighted.